Fiscal policy measures in the Corona virus period - Ćeha Nikola; Ćeha Milenko (Trendovi u Poslovanju)
Fiscal policy measures are necessary weapons to overcome the economic crisis caused by the Coronavirus. State intervention and implementation of adequate measures can significantly protect the domestic economy and thus speed up the recovery. The focus of the paper are the fiscal policy measures implemented by the Republic of Serbia during and after the introduction of the state of emergency, as well as plans for the measures in the future. As a country in transition with lower economic growth than other EU member states, Serbia has followed the trends of implementing fiscal policy measures following the example of the most powerful economies in the world. Relevant international and domestic sources were used for the analysis. The results of the research show that Serbia has implemented adequate measures to overcome the crisis, but in comparison with the countries of the European Union, providing financial resources is one of the biggest problems in the given period.